Estimating the future with the Sustainability assessment methodology to soil-associated agricultural experiments - Hoogenboom, Gerrit; Rodríguez-Roa, Andrea Onelia; Castillo Romero, Oscar Gonzalo; Monsalve Camacho, Oscar Iván (John Wiley and Sons Ltd, 2025)
Agricultural sustainability assessments have gained high importance during the last decades. Different tools have been developed for these assessments such as the Sustainability assessment methodology oriented to soil-associated agricultural experiments (SMAES). SMAES quantifies the current sustainability of the different treatments evaluated in experiments associated with the soil. However, efforts aimed to maintain or increase the crop systems sustainability must be planned and measured in the short, medium, and long-term. In this work, some parameters are added to SMAES to estimate the future sustainability. The first parameter is the construction of climate scenarios (RCP 4.5 and 8.5, model CCSM4, periods 2050-2100) to establish the conditions of change in the future. Second, crop yield is modelled with DSSAT (Decision Support System for Agrotechnology Transfer) using the aforementioned climate scenarios. Third, yield modelling results and SMAES sustainability indexes (IS) from climate scenarios are integrated. As a case of study, the current sustainability (IS-A) of five potato fertilization split treatments were initially estimated: Commercial control (Control), Fertilization recommended by Agrosavia (As), Monthly split fertilization recommended by Agrosavia (AsSplit), AsSplit decreasing the amount of fertilizer by 25% (AsSp25), and AsSplit decreasing the amount of fertilizer by 50% (AsSp50). AsSp50 generated the highest current and future sustainability with IS-A = 0.90, IS-45, and IS-85 = 0.88. Results suggest that integrated fertilization management practices generate a higher potato crop sustainability in the Colombian high Andean, both today and the future.